Non-performing loans in European Union: country governance dimensions - Lee, Yok Yong; Yahya, Mohd Hisham; Habibullah, Muzafar Shah; Mohd Ashhari, Zariyawati (Emerald Group Publishing, 2019)
Purpose – This paper aims to provide new empirical evidence on the non-performing loan (NPL) determinants of the EU conventional banks, in the context of macroeconomic factors, dimensions of country governance and bank-specific characteristics. Design/methodology/approach – The panel data sets of 1,053 conventional banks were obtained over the period of 2007-2016. The Hodrick–Prescott filter was adopted to extract business cycle and credit cycle from real gross domestic product and credit to the private non-financial sector, correspondingly. System-generalised methods of moment was then used to identify the significant determinants of NPL. Findings – The empirical results reveal that NPL is primarily driven positively by lagged-one NPL and risk profile. In consonance with the skimping hypothesis, NPL has a significant positive relationship with the cost efficiency. The empirical finding of the business cycle coincides with the Austrian business cycle theory. Particularly, NPL is relatively low during rapid economic growth of credit-sourced business boom. Whereas, business bust happens when credit creation runs its course and is associated with high NPL. This paper encapsulates that NPL is driven by not only macroeconomic factors and bank-specific characteristics but also the dimensions of country governance. Practical implications – Policymakers should introduce policies that are geared towards proper dimensions of country governance. Originality/value – The novelty of this research does not rely on the multidimensions of NPL determinants but on the disentanglement of the conventional banks with dual identity (i.e. Islamic banks, cooperative banks and ethical banks). It considers business cycle, credit cycle and previous NPL as the potential determinants.